ED-DHENTYS (Education Dental Health System) Model As An Effort To Change Behavior In The Implementation Of Oral Hygiene Through A Family-Centered Care Approach In Bima Regency, NTB - Jumiati Jumiati; Endah Aryati; Lanny Sunarjoi (Journal Of Social Science (JoSS), 2023)
Background : Oral hygiene is still a major problem for the elderly. Riskesdas in 2018 said dental problems in the age group of 55-64 increased 48.5% and ages 65 and above by 38.6%. Various dental health services programs continue to be developed to reduce dental and oral health problems, including by improving the quality of the media used. The relevant media used today is technology-base media. Aim : Producing Ed-Dhentys models as a medium of education in changing the behavior of implementing oral hygiene for the elderly through a family centered care approach. Method : Research and Development (R&D) with Quasy experiment Pretest-Posttest group design. Variables in this study : Knowledge, attitude, brushing skills and debris index. There research project was 2 group : intervention 16 people given Ed-Dhentys Model and Control 16 people given Slide power point. Data tested using Wilcoxon and Mann-Whitney. They hypothesis test meaningfulness criterion uses the p-value 0.002 of the delta value (?). Result : The Ed-Dhentys model is feasible as a dental health education media with expert validation results of 92% and a p-value of and unpaired test results stating that this application is effective in increasing knowledge (?=6.81), attitude (?= 13.75), brushing skills (?6.93), and decreasing the debris index score (?=1.37) compared to the control group. Conclusion : The Ed-Dhentys model proved feasible and its application was effective as an effort to improve behavior in the implementation of oral hygiene and a decrease in debris index in adolescents compared to the contol group.